THE ORIGIN OF A NEW RELATIVITY. NO SENSE OF EINSTEIN'S PRINCIPLES OF RELATIVITY - Fernandes, José Luís Pereira Rebelo (International Journal of Research -GRANTHAALAYAH, 2021)
Based on the analysis of “The contraction of time under the action of a gravi- tational field, in different references at rest”, we conclude that space does not contract. In view of the result obtained, we were obliged to analyze the found- ing principles of Einstein’s theory of relativity, the dilation of time and the con- traction of space, the two principles, structural pillars of the whole theory of relativity. We found problems in the model regarding the relativity of time in the direc- tion of displacement. It is proposed for the calculation of time in the stopped frame the contraction of time in the moving frame which is contrary to the model. We also analyzed Michelson-Morley’s experience and concluded that it does not respect the principle of time expansion for a K in the direction of dis- placement. Finally, we decided to look with double attention to the meaning of the expression of time dilation, concluding once again that space does not heal and that the principle to be retained is the constancy of space covered by ”light” in the equivalent times of all reference frames. We conclude that we have a new way of looking at physics, which will give rise to a new theory of relativity.